اقتراح نموذج وصفي رقمي للمظاهر الجيوكارستية في مغارة بيت الوادي-المنطقة الساحلية (Latakia University Journal -Basic Sciences Series, 2014)
تعتبر مغارة بيت الوادي, الواقعة في قلب السلسة الساحلية على بعد 40 كم إلى الشرق من طرطوس، مع ما تتضمنه من تنوعٍ جيوكارستي، من أهم المظاهر الكارستية في المنطقة الساحلية كماً ونوعاً .تتموضع ضمن بنية جيولوجية شديدة التعقيد, وتقطعها مجموعة من الفوالق التي تعتبر من الأسباب الرئيسية لتطورها. ليتولوجياً تعود للألبيان، المكون من الحجر الكلسي، والكلسي المدلمت، المشوب بالغضاريات، مع وجود تخططات بازلتية قاطعة للمغارة. تعكس مورفولوجية المغارة أشكالاً كارستية معقدة جداً ضمن الصخور الكربوناتية، تأخذ اتجاه شمال – جنوب. يخترقها نهر جوفي، وتشهد جريان سطحي وجوفي مرتبط بالهاطل المطري كما تؤكد الينابيع المنتشرة في المنطقة كنبع السودة. تقدم المغارة مع خصائصها الجيوكارستية نموذجاً كارستياً متكاملاً لاحتوائها على أغلب المظاهر الكارستية. سمحت هذه الدراسة، باستخدام تقنيات وبرمجيات حديثة، بوضع مجسم ثلاثي الأبعاد، واقتراح نموذج رقمي يقدم تصنيفاً واضحاً ودقيقاً لأجزاء المغارة، ويمثل دليلاً نموذجياً لدراسات من هذا النوع في سورية وغيرها. Baet Alwadi cavern, located in the central part of the coastal chain, at40km.to the east of Tartous city, with its geoKarstic diversity, is the most important Karst phenomena in the coastal area. It represents a complex geological structure, affected by clear faults, which are the main reasons of its development. Lithologicaly, it belong to the alpian age, constituted of limestone and dolo-limestone tinged with clay, associated to basalt sills, which cross it. The cavern morphology indicates a complex shapes within the carbonate rocks, taking the direction North-South. An underground river passes through the cavern, in addition to a ground and underground flowing, due to the rainfall water precipitation indicated by the occurred springs in  the region as Al Saouda spring. The cavern is a typical karstic integrated model, showing the most karst phenomena. This study allowed, using modern techniques and software, the development of a three-dimensional model, and consequentially a numerical model permitting a clear and precise classification of the caverns, in Syria and others countries.